The European Neuroendocrine Tumour Society registry, a tool to assess the prognosis of neuroendocrine neoplasms. (June 2022) - Borbath, Ivan; Garcia-Carbonero, Rocio; Bikmukhametov, Damir; Jimenez-Fonseca, Paula; Castaño, Angel; Barkmanova, Jaroslava; Sedlackova, Eva; Kollár, Attila; Christ, Emanuel; Kaltsas, Gregory; Kos-Kudla, Beata; Maasberg, Sebastian; et al.
Abstract: Background: Neuroendocrine neoplasms (NENs) are rare tumours with variable clinical behaviour. Their natural history is ideally best approached in large, multicentre and multinational registries with long-term patients' follow-up. The European Neuroendocrine Tumour Society registry aims to obtain information regarding NEN outcomes and prognostic factors in a European frame. Patients and methods: We collected data from 7 national NEN registries (Belgium, Czech Republic, Germany, Greece, Poland, Spain, Switzerland), representing 10, 102 patients. Anonymised/pseudonymised data were collected in a secured server. Descriptive statistical methods were applied, as well as Kaplan–Meier survival curves and multivariable analyses for prognostic factors of overall survival (OS). Results: median age of the study population was 60 years (range: 18–102), 48% were female. Common primary tumour sites were pancreas (27%) and small intestine (21%). Stage 4 disease was found in 47% of patients, while 26/10/16% had stage 1/2/3 disease, respectively. Grading (n = 6952) was G1/2/3 in 48/37/15% of the patients, respectively. Surgery was the main treatment, provided to 71% of patients, followed by somatostatin analogues (32%), chemotherapy (20%), Peptide receptor Radionuclide Therapy (PRRT) (9%) and targeted therapies (8%). OS at 5 years was 74%, influenced by grade, stage and tissue of origin in multivariate analysis. A Ki67 cut-off value set at 55% within the G3 group allowed to separate 2 groups with a meaningful different OS. Conclusion: We report the first analysis of the European Neuroendocrine Tumour Society registry, comprising 10, 102 patients with NEN from 7 European countries. This large cohort study describes prognostic factors for the survival of NENs throughout Europe, including primary tumour site, grade, stage and treatment. Highlights: The European Neuroendocrine Tumour Society registry is a multinational database, under the umbrella of European Neuroendocrine Tumour Society. We analysed 10, 102 patients, providing data on grade, stage, treatment and survival. Survival is influenced by clinical stage 4, pathological grade 3 and organ of origin. A 55% Ki67 cut-off distinguishes 2 groups of patients with G3 and with different prognosis. Concerning patients with G2, 3 Ki67 cut-offs lead to distinctive overall survival.